Dust-proof and sweat-proof functional material for Bluetooth headset shell and preparation method thereof
By using functional materials prepared with specific ratios of polypropylene and modification additives, the problem of insufficient sweat resistance and antistatic properties of the Bluetooth headphone shell is solved, and higher sweat resistance, antistatic and mechanical properties are achieved, and the headphones are extended. service life.
Patent Information
- Application Number
- CN202410703944.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-01
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-06-01
AI Technical Summary
The material of Bluetooth headphone shell has poor sweat resistance and anti-static properties, resulting in sweat penetration and damage caused by static electricity.
50 to 70 parts of polypropylene, 8 to 12 parts of maleic anhydride grafted polypropylene, 5 to 7 parts of composite modified agent, 4 to 6 parts of inorganic modified additives, 0.5 to 1.5 parts of antioxidant, 3 to 5 parts of The ratio of lubricant and 2 to 4 parts of colorant is made by preparing a composite modified agent and an inorganic modified additive to form a functional material with low surface energy and antistatic properties, and is used for extrusion and granulation of Bluetooth headphone shells.
It effectively improves sweat resistance, prevents sweat penetration and static damage, enhances anti-static and dust resistance, extends the service life of the headphones, and improves impact and mechanical properties.
Smart Images

Figure CN118515934B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a dustproof and sweatproof functional material for a Bluetooth headset shell and a preparation method thereof. Background Art
[0002] Bluetooth headsets are a type of wireless headset that uses Bluetooth technology to achieve wireless transmission of audio signals. They are loved by users for their lightness, portability, and freedom from cable constraints, and are used in an increasingly wide range of applications. The outer shell of a Bluetooth headset is in direct contact with the outside world, so it plays a vital role in protecting the internal components of the headset. With the development of the economy, people's demand for Bluetooth headsets is also growing, and at the same time, the requirements for their quality are also increasing. As an important component of the headset, the performance of the Bluetooth headset outer shell directly affects the overall quality and reliability of the headset. Therefore, the performance requirements for the Bluetooth headset outer shell are also getting higher and higher.
[0003] Polypropylene, a polymer material, has become the preferred material for preparing Bluetooth headset shells because of its advantages such as being non-toxic, odorless, good insulator, light weight, and easy processing. When users use Bluetooth headsets during exercise or in a hot environment, the Bluetooth headset shell needs to have excellent sweat-proof properties to prevent sweat from penetrating into the inside of the headset, causing short circuits, corrosion, performance degradation, or even damage to the headset. In addition, polypropylene has poor anti-static properties and is prone to generating static electricity on the surface. Static electricity will attract surrounding dust particles and cause them to adhere to the headset shell. The dust may enter the headset through the gaps or interfaces of the shell, causing problems such as degraded sound quality, component short circuits, and damage, thereby affecting its use.
[0004] Therefore, when using polypropylene material to prepare the Bluetooth headset shell, it is usually modified. For example, the invention patent with publication number CN105968567B discloses an antistatic masterbatch and its preparation method and application. The invention prepares the antistatic masterbatch by blending the antistatic agent, polypropylene resin and auxiliary agent, and melt extruding and granulating. When the antistatic masterbatch is used in the injection molding product processing industry, it overcomes the static electricity generated by the polymer material due to friction, and also makes the product itself have a certain antistatic effect, and also has a good effect on the surface dustproof of the product. Based on this, it is of great significance for the present invention to prepare a functional material with excellent anti-sweat performance and antistatic performance. Summary of the invention
[0005] The purpose of the present invention is to provide a dustproof and sweatproof functional material for a Bluetooth headset housing and a preparation method thereof, which solves the following technical problems:
[0006] (1) The problem of poor sweat resistance of Bluetooth headset shell materials is solved;
[0007] (2) The problem of poor antistatic properties of Bluetooth headset shell materials has been solved;
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] A dustproof and sweatproof functional material for a Bluetooth headset shell comprises the following raw materials in parts by weight: 50 to 70 parts of polypropylene, 8 to 12 parts of maleic anhydride grafted polypropylene, 5 to 7 parts of a composite modifier, 4 to 6 parts of an inorganic modified additive, 0.5 to 1.5 parts of an antioxidant, 3 to 5 parts of a lubricant, and 2 to 4 parts of a colorant.
[0010] Furthermore, the preparation method of the composite modifier comprises the following steps:
[0011] A1: Mix the perfluoropolyether carboxylic acid and toluene solution, stir evenly, then add glycidyl furfural ether and catalyst, raise the temperature to 90-100°C, keep stirring for 2-4 hours, and remove the solvent by vacuum distillation to obtain modified perfluoropolyether carboxylic acid;
[0012] A2: Add the modified perfluoropolyether carboxylic acid to N,N-dimethylformamide, stir mechanically, pass nitrogen, exhaust the air, add methyltrichlorosilane and acid binding agent, raise the temperature to 55-65°C, keep stirring at this temperature for 3-5 hours, wait for the material to cool naturally, discharge the material, and obtain the composite improver.
[0013] Furthermore, in step A1, the number average molecular weight of the perfluoropolyether carboxylic acid is 1000 to 3000.
[0014] Furthermore, in step A1, the catalyst is any one of boron trifluoride etherate, tetramethylammonium bromide or tetrabutylammonium hydrogen sulfate.
[0015] Furthermore, in step A2, the acid binding agent is any one of pyridine or triethylamine.
[0016] Through the above technical scheme, under the action of a catalyst, the carboxyl group in the perfluoropolyether carboxylic acid structure can undergo a ring-opening esterification reaction with the epoxy group in the glycidyl furfural ether structure, thereby introducing active hydroxyl groups into the perfluoropolyether carboxylic acid structure to obtain a modified perfluoropolyether carboxylic acid. Under the action of an acid-binding agent, the active hydroxyl groups in the modified perfluoropolyether carboxylic acid structure can react with the silicon chlorine in the methyltrichlorosilane structure to obtain a composite improver.
[0017] Furthermore, the preparation method of the inorganic modified additive comprises the following steps:
[0018] AA1: Add carbon fiber and acetone into the reactor, extract for 45 to 50 hours, wash and dry, then place the dried carbon fiber in a concentrated nitric acid solution, keep it warm at 85 to 95°C for 1 to 3 hours, take it out and wash it with deionized water until the pH value is 5.5 to 6.5, to obtain pretreated carbon fiber;
[0019] AA2: The pretreated carbon fiber is ultrasonically dispersed in dimethyl sulfoxide to form a dispersion, polyisobutylene succinimide and a condensation agent are added to the dispersion, and stirred at room temperature for 4 to 8 hours under nitrogen protection. The nitrogen is removed, the solid material is separated, the solid material is washed, and vacuum dried to obtain an inorganic modified additive.
[0020] Furthermore, in step AA1, the carbon fiber has a diameter of 1 to 10 μm and a length of 1 to 5 mm.
[0021] Furthermore, in step AA1, the mass fraction of the concentrated nitric acid solution is 60% to 70%.
[0022] Furthermore, in step AA2, the condensing agent is any one of N,N-dicyclohexylcarbodiimide or 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride.
[0023] Through the above technical scheme, under the action of the condensation agent, the carboxyl groups on the surface of the pretreated carbon fiber can react with the imino groups in the polyisobutylene succinimide structure, thereby grafting the polyisobutylene succinimide to the surface of the carbon fiber to obtain an inorganic modified additive.
[0024] A method for preparing a dust-proof and sweat-proof functional material for a Bluetooth headset shell comprises the following steps:
[0025] (1) adding polypropylene, maleic anhydride grafted polypropylene, composite modifier and inorganic modified additive into a mixer, setting the mixer speed to 300-500 r / min, stirring for 30-50 min, adding antioxidant, lubricant and colorant, and continuing to stir and mix for 20-40 min to obtain a premix;
[0026] (2) placing the premix obtained in step (1) in an extruder, setting the barrel temperature of the extruder to 110-120° C. and the head temperature to 120-130° C., performing extrusion granulation, and allowing the material to cool naturally to obtain a functional material.
[0027] Beneficial effects of the present invention:
[0028] (1) The present invention prepares a composite modifier as an antiperspirant for a functional material. Since the composite modifier contains a large amount of CF bonds and siloxane structures, the functional material has an extremely low surface energy. It is difficult for sweat to form continuous water droplets on the surface of the material, but it is in a discrete state, thereby effectively preventing the accumulation and penetration of sweat. Therefore, the composite modifier is used to prepare a Bluetooth headset shell, which can effectively improve the anti-perspirant performance of the headset shell and prevent sweat from penetrating into the inside of the headset, causing short circuits, performance degradation, damage, etc. At the same time, the furan ring in the composite modifier structure can improve the anti-fouling performance of the material, effectively preventing the adhesion and accumulation of pollutants such as grease and water, thereby extending the service life of the Bluetooth headset.
[0029] (2) The present invention forms an inorganic protective layer in the matrix by adding an inorganic modified additive during the preparation of the functional material. The carbon fiber in the inorganic modified additive has good interface properties with the polypropylene matrix after organic modification, and can be relatively evenly dispersed in the polypropylene matrix to form a good filling effect. On the one hand, the carbon fiber can improve the antistatic performance of the functional material, so that the prepared Bluetooth headset shell has good antistatic ability, avoiding dust adhering to the headset shell due to static electricity, thereby protecting the internal components of the headset from dust damage, and at the same time having a good effect on the surface dustproof of the headset. On the other hand, the inorganic modified additive enhances the rigidity and impact resistance of the functional material, avoiding deformation, cracks or damage to the headset shell when subjected to external force. At the same time, the hydroxyl group, imine group and other groups in the inorganic modified additive can form hydrogen bonds with the maleic anhydride group in the matrix, further enhancing the mechanical properties of the functional material such as impact resistance. The improvement of these properties not only improves the protective performance of the Bluetooth headset, but also brings a better user experience to the user.
[0030] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0032] Figure 1 This is an infrared spectrum test chart of the modified perfluoropolyether carboxylic acid and the composite modifier prepared in Example 1 of the present invention.
[0033] Figure 2 This is a scanning electron microscope image of the carbon fiber and inorganic modified additive prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] 1. Preparation of composite improver
[0037] A1: 10 g of a perfluoropolyether carboxylic acid having a number average molecular weight of 2000 and a toluene solution were mixed and stirred evenly, and then 1.6 g of glycidyl furfuryl ether and 0.1 g of boron trifluoride ether were added. After the addition was completed, the temperature was raised to 95° C., the mixture was stirred for 3 h, and the solvent was removed by reduced pressure distillation to obtain a modified perfluoropolyether carboxylic acid;
[0038] A2: Add 5g of modified perfluoropolyether carboxylic acid to N,N-dimethylformamide, stir mechanically, pass nitrogen, exhaust the air, add 0.8g of methyltrichlorosilane and 0.05g of pyridine, raise the temperature to 60°C, keep stirring at this temperature for 4h, wait for the material to cool naturally, discharge the material, and obtain a composite improver.
[0039] The modified perfluoropolyether carboxylic acid and the composite modifier were characterized by infrared spectrometer Nicolet IS10. The test results are shown in Figure 1 ,Depend on Figure 1 It can be seen that in the infrared spectrum of modified perfluoropolyether carboxylic acid, 1230 cm -1 The absorption peak of CF bond appears at 1064cm -1 The absorption peak of ether bond COC appears at 1758 cm -1 The characteristic absorption peak of the ester group C=O appears at 3125cm -1 and 3150cm -1 The absorption peak of the carbon-hydrogen bond in the furan ring appears at 3282 cm -1 The absorption peak of hydroxyl group OH appears at 1083cm -1 The absorption peak of ether bond COC appears at 3120 cm -1 and 3155cm -1 The absorption peak of the carbon-hydrogen bond in the furan ring appears at 1741 cm -1 The characteristic absorption peak of the ester group C=O appears at 1014 cm -1 The absorption peak of SiO appears at the center, and the absorption peak of the hydroxyl group disappears.
[0040] 2. Preparation of Inorganic Modified Additives
[0041] AA1: Add 5 g of carbon fiber with a diameter of 4 μm and a length of 2 mm and acetone into the reactor, extract for 48 hours, wash and dry, and then place the dried carbon fiber in a concentrated nitric acid solution with a mass fraction of 65%, keep it warm at 90°C for 2 hours, take it out and wash it with deionized water to a pH value of 6 to obtain pretreated carbon fiber;
[0042] AA2: Ultrasonic disperse 3 g of pretreated carbon fiber in dimethyl sulfoxide to form a dispersion, add 2.6 g of polyisobutylene succinimide and 0.1 g of N,N-dicyclohexylcarbodiimide to the dispersion, stir at room temperature for 6 h under nitrogen protection, remove the nitrogen, separate the solid material, wash the solid material, and vacuum dry to obtain an inorganic modified additive.
[0043] The morphology of carbon fiber and inorganic modified additives was analyzed using a SU8020 field emission scanning electron microscope produced by Hitachi. The test results are shown in Figure 2 As can be seen from the figure, the surface of carbon fiber is relatively smooth, while the surface morphology of inorganic modified additives changes significantly and becomes rough. This is because polyisobutylene succinimide is grafted onto the surface of carbon fiber.
[0044] 3. Preparation of functional materials
[0045] (1) 50 g of polypropylene, 8 g of maleic anhydride grafted polypropylene, 5 g of composite modifier and 4 g of inorganic modified additive were added to a mixer, the speed of the mixer was set to 300 r / min, and after stirring for 30 min, 0.5 g of antioxidant 1010, 3 g of paraffin and 2 g of titanium dioxide were added, and stirring and mixing were continued for 20 min to obtain a premix;
[0046] (2) placing the premix obtained in step (1) in an extruder, setting the barrel temperature of the extruder to 110° C. and the head temperature to 120° C., performing extrusion granulation, and allowing the material to cool naturally to obtain a functional material.
[0047] Example 2
[0048] Preparation of functional materials
[0049] (1) 60 g of polypropylene, 10 g of maleic anhydride grafted polypropylene, 6 g of a composite modifier and 5 g of an inorganic modified additive were added to a mixer, the mixer speed was set to 400 r / min, and after stirring for 40 min, 1 g of an antioxidant 1010, 4 g of paraffin and 3 g of titanium dioxide were added, and the stirring and mixing was continued for 30 min to obtain a premix;
[0050] (2) placing the premix obtained in step (1) in an extruder, setting the barrel temperature of the extruder to 115° C. and the head temperature to 125° C., performing extrusion granulation, and allowing the material to cool naturally to obtain a functional material.
[0051] The preparation method of the composite modifier and the inorganic modified additive is the same as that in Example 1.
[0052] Example 3
[0053] Preparation of functional materials
[0054] (1) 70 g of polypropylene, 12 g of maleic anhydride grafted polypropylene, 7 g of a composite modifier and 6 g of an inorganic modified additive were added to a mixer, the speed of the mixer was set to 500 r / min, and after stirring for 50 min, 1.5 g of an antioxidant 1010, 5 g of paraffin and 4 g of titanium dioxide were added, and the stirring and mixing was continued for 40 min to obtain a premix;
[0055] (2) placing the premix obtained in step (1) in an extruder, setting the barrel temperature of the extruder to 120° C. and the head temperature to 130° C., performing extrusion granulation, and allowing the material to cool naturally to obtain a functional material.
[0056] The preparation method of the composite modifier and the inorganic modified additive is the same as that in Example 1.
[0057] Comparative Example 1
[0058] Preparation of functional materials
[0059] (1) 60 g of polypropylene, 10 g of maleic anhydride grafted polypropylene, and 6 g of a composite modifier were added to a mixer, the speed of the mixer was set to 400 r / min, and after stirring for 40 min, 1 g of an antioxidant 1010, 4 g of paraffin wax, and 3 g of titanium dioxide were added, and the stirring and mixing was continued for 30 min to obtain a premix;
[0060] (2) placing the premix obtained in step (1) in an extruder, setting the barrel temperature of the extruder to 115° C. and the head temperature to 125° C., performing extrusion granulation, and allowing the material to cool naturally to obtain a functional material.
[0061] The preparation method of the composite modifier is the same as that in Example 1.
[0062] Comparative Example 2
[0063] Preparation of functional materials
[0064] (1) 60 g of polypropylene, 10 g of maleic anhydride grafted polypropylene, and 5 g of inorganic modified additive were added to a mixer, the speed of the mixer was set to 400 r / min, and after stirring for 40 min, 1 g of antioxidant 1010, 4 g of paraffin wax, and 3 g of titanium dioxide were added, and the stirring and mixing were continued for 30 min to obtain a premix;
[0065] (2) placing the premix obtained in step (1) in an extruder, setting the barrel temperature of the extruder to 115° C. and the head temperature to 125° C., performing extrusion granulation, and allowing the material to cool naturally to obtain a functional material.
[0066] The preparation method of the inorganic modified additive is the same as that in Example 1.
[0067] Comparative Example 3
[0068] Preparation of functional materials
[0069] (1) 60 g of polypropylene, 10 g of maleic anhydride grafted polypropylene, 6 g of composite modifier and 5 g of carbon fiber were added to a mixer, the speed of the mixer was set to 400 r / min, and after stirring for 40 min, 1 g of antioxidant 1010, 4 g of paraffin and 3 g of titanium dioxide were added, and stirring and mixing continued for 30 min to obtain a premix;
[0070] (2) placing the premix obtained in step (1) in an extruder, setting the barrel temperature of the extruder to 115° C. and the head temperature to 125° C., performing extrusion granulation, and allowing the material to cool naturally to obtain a functional material.
[0071] The preparation method of the composite modifier is the same as that in Example 1.
[0072] Comparative Example 4
[0073] Preparation of functional materials
[0074] (1) 60 g of polypropylene and 10 g of maleic anhydride grafted polypropylene were added to a mixer, the speed of the mixer was set to 400 r / min, and after stirring for 40 min, 1 g of antioxidant 1010, 4 g of paraffin and 3 g of titanium dioxide were added, and the stirring and mixing was continued for 30 min to obtain a premix;
[0075] (2) placing the premix obtained in step (1) in an extruder, setting the barrel temperature of the extruder to 115° C. and the head temperature to 125° C., performing extrusion granulation, and allowing the material to cool naturally to obtain a functional material.
[0076] Performance Testing
[0077] The functional materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 were injection molded into samples that met the test specifications. The samples were subjected to an impact strength test according to GB / T 1843-2008 "Determination of Izod Impact Strength of Plastics"; the samples were subjected to a tensile strength test according to GB / T 1040.1-2018 "Determination of Tensile Properties of Plastics Part 1: General Principles", with the tensile rate set to 100 mm / min; the samples were subjected to a bending strength test according to GB / T 9341-2008 "Determination of Bending Properties of Plastics"; the samples were subjected to a water contact angle test using a JC2000D2G contact angle tester; the samples were subjected to a high resistance meter MCP-HT450 at a voltage of 250 V under the conditions of a temperature of 25°C and a relative humidity of 60%, and the initial surface resistivity of the samples was measured. The specific test results are shown in the following table:
[0078]
[0079] As can be seen from the above table, the samples prepared in Examples 1 to 3 all have excellent anti-perspiration performance, antistatic performance and mechanical properties; in the sample prepared in Comparative Example 1, no inorganic modified additive was added, and compared with the example, its surface resistivity was relatively high, and the numerical values of impact strength, tensile strength and flexural strength decreased greatly, and the antistatic performance and mechanical properties of the sample were poor, but a composite modifier was added therein, so the anti-perspiration performance of the sample was good; in the sample prepared in Comparative Example 2, no composite modifier was added, and compared with the example, the anti-perspiration performance of the sample was poor, but an inorganic modified additive was added, so the anti-static performance and mechanical properties of the sample were good; in Comparative Example 3, a composite modifier and carbon fiber were used for filling, and compared with the example, the antistatic performance and mechanical properties of the sample were general, and the anti-perspiration performance was good. It is speculated that this may be because the carbon fiber was not modified, and agglomeration occurred in the matrix, resulting in a decrease in the antistatic performance and mechanical properties of the sample; in the sample prepared in Comparative Example 4, no composite modifier and inorganic modified additive were added, so the performance of each sample was the worst.
[0080] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A dustproof and sweatproof functional material for a Bluetooth headset housing, characterized in that: The invention comprises the following raw materials in parts by weight: 50 to 70 parts of polypropylene, 8 to 12 parts of maleic anhydride grafted polypropylene, 5 to 7 parts of composite improver, 4 to 6 parts of inorganic modified additive, 0.5 to 1.5 parts of antioxidant, 3 to 5 parts of lubricant, and 2 to 4 parts of colorant; The preparation method of the composite modifier comprises the following steps: A1: Mix the perfluoropolyether carboxylic acid and toluene solution, stir evenly, then add glycidyl furfural ether and catalyst, raise the temperature to 90-100°C, keep stirring for 2-4 hours, and remove the solvent by vacuum distillation to obtain modified perfluoropolyether carboxylic acid; A2: Add the modified perfluoropolyether carboxylic acid to N,N-dimethylformamide, stir mechanically, pass nitrogen, exhaust the air, add methyltrichlorosilane and acid binding agent, raise the temperature to 55-65°C, keep stirring at this temperature for 3-5 hours, wait for the material to cool naturally, discharge the material, and obtain the composite improver; The catalyst is any one of boron trifluoride etherate, tetramethylammonium bromide or tetrabutylammonium hydrogen sulfate; The preparation method of the inorganic modified additive comprises the following steps: AA1: Add carbon fiber and acetone into the reactor, extract for 45 to 50 hours, wash and dry, then place the dried carbon fiber in a concentrated nitric acid solution, keep it warm at 85 to 95°C for 1 to 3 hours, take it out and wash it with deionized water until the pH value is 5.5 to 6.5, to obtain pretreated carbon fiber; AA2: ultrasonically dispersing the pretreated carbon fiber in dimethyl sulfoxide to form a dispersion, adding polyisobutylene succinimide and a condensing agent to the dispersion, stirring at room temperature for 4 to 8 hours under nitrogen protection, removing the nitrogen, separating the solid material, washing the solid material, and vacuum drying to obtain an inorganic modified additive; The condensing agent is any one of N,N-dicyclohexylcarbodiimide and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride.
2. The dust-proof and sweat-proof functional material for a Bluetooth headset housing according to claim 1, characterized in that: In step A1, the number average molecular weight of the perfluoropolyether carboxylic acid is 1000-3000.
3. The dust-proof and sweat-proof functional material for a Bluetooth headset housing according to claim 1, characterized in that: In step A2, the acid binding agent is any one of pyridine or triethylamine.
4. The dust-proof and sweat-proof functional material for a Bluetooth headset housing according to claim 1, characterized in that: In step AA1, the diameter of the carbon fiber is 1 to 10 μm and the length is 1 to 5 mm.
5. The dust-proof and sweat-proof functional material for a Bluetooth headset housing according to claim 1, characterized in that: In step AA1, the mass fraction of the concentrated nitric acid solution is 60% to 70%.
Citation Information
Patent Citations
An antistatic masterbatch, its preparation method and application
CN105968567B
Double-end perfluoropolyether silane and preparation method thereof
CN111057230A
Electric appliance shell based on composite material and production process thereof
CN118027541A